In order to stand up you must keep cycling: Change and coordination in complex evolving economies - Giovanni Dosi; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
In this work we discuss the main building blocks, achievements and challenges of an evolutionary interpretation of the relation between mechanisms of coordination and drivers of change in modern economies, seen as complex evolving systems. It is an evident stylised fact of modern economic systems that there are forces at work which keep them together and make them grow despite rapid and profound modifications of their industrial structures, social relations, techniques of production, patterns of consumption. We suggest that a fruitful interpretation of the two processes rests in what we call the "bicycle conjecture": in order to stand up you must keep cycling. However, changes and transformation are by nature "disequilibrating" forces. Thus there must be other factors which maintain relatively ordered configurations of the system and allow a broad consistency between the conditions of material reproduction (including income distributions, accumulation, available techniques) and the thread of social relations.
Keywords: O1; O3; P1; 330; Change; Coordination; Evolutionary Economics; Socio-Economic Systems